Returns on investments in new ski lifts: The importance of weather conditions and elevation - Martin Falk (European Regional Science Association (ERSA), 2015)
This paper investigates the factors that influence the change in passenger ski-lift transports between a normal winter and an anomalously mild winter based on individual lift and aggregate ski-area data. Special focus is placed on the return on investments in new ski lifts. Using endogenous treatment effects models, we find large average treatment effects for ski lifts at the individual level (including a difference of about 90 percentage points in growth rate). At the aggregate ski-area level, however, no significant output effects can be detected. This indicates that the indirect business-stealing effect outweighs the direct expansion effect. Furthermore, the change in ski-lift output between anomalously warm and normal winter seasons depends positively and non-linearly on the average elevation of the ski lift at hand. Growth in passenger numbers is independent from an elevation of 2,365 metres or higher for existing lifts and 1685 metres for new ski lifts. A large number of guest beds and a high share of slopes covered by snowmaking equipment also have positive effects on changes in ski-lift transports. The probit model shows that ski lifts with a high number of passengers in the beginning of the period, as well as older and smaller lifts, are more likely to be replaced.
Keywords: D22; D24; O33; L25; L92; 330; firm growth; endogenous treatment effects model; winter tourism; climate change